Developing a Strategic Framework for Mapping Sustainable Business Opportunities in Islamic Higher Education Institutions under the Badan Layanan Umum (BLU) Scheme - Yayan Mulyana (Khazanah Sosial, 2025)
This study aims to develop a strategic, ethical, and sustainability-oriented conceptual framework for identifying and evaluating sustainable business opportunities within Indonesian Islamic Higher Education Institutions operating under the Public Service Agency (PTKI BLU) model. Amid rising pressures on higher education institutions to reduce reliance on public funding and enhance revenue diversification, PTKI BLUs face the unique challenge of balancing market responsiveness with strict adherence to Islamic values and broader sustainability imperatives. This research adopts a qualitative conceptual approach inspired by Jabareen’s framework analysis method, integrating extensive literature reviews and secondary data from institutional reports, policy documents, and best practices across PTKI BLUs. The findings result in a multidimensional framework composed of four core dimensions: (1) Internal Resource Audit, (2) External Needs & Market Analysis, (3) Business Model Development with a triple-filter evaluation (BLU Feasibility, Islamic Value Congruence, and Sustainability Impact), and (4) Strategic Prioritization, Implementation, and Monitoring. This framework assists PTKIs in strategically transforming internal assets—academic expertise, physical infrastructure, networks, and Islamic identity—into mission-aligned and financially viable ventures across sectors such as halal industry, Sharia finance, education services, and community-based enterprises. The implications of this study are twofold: it offers a roadmap for PTKIs to enhance their institutional resilience through ethically grounded entrepreneurship, and it contributes to the discourse on Islamic university governance under autonomy models like BLU. The originality of this research lies in its integrated approach, bridging regulatory flexibility, Islamic ethical principles, and sustainability into a unified model—addressing a critical theoretical and practical gap in current higher education and Islamic management scholarship.